Development of satranidazole mucoadhesive gel for the treatment of periodontitis - Bansal K.; Rawat M.K.; Jain A.; Rajput A.; Chaturvedi T.P.; Singh S. (My University, 2025)
The aim of the paper was to develop satranidazole-containing mucoadhesive gel for the treatment of periodontitis. Different mucoadhesive gels were prepared, using various gelling agents like sodium carboxymethylcellulose (SCMC), poloxamer 407, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, and the mucoadhesive polymer carbopol 934P. The selected formulations (based on the mucoadhesive force) were studied for different mechanical properties, such as mucoadhesive strength, hardness, compressibility, adhesiveness, and cohesiveness through Texture Profile Analyzer. In vitro satranidazole release from the prepared formulations was also determined and compared with marketed preparation of metronidazole (Metrogyl® gel). The formulation SC30 (containing SCMC 3% w/v) showed maximum mucoadhesive strength (167.72 ± 3.76 g) and adhesiveness (-46.23 ± 0.34 N∈mm), with low hardness (9.81 ± 0.04 N) and compressibility (40.05 ± 0.48 N∈mm) and moderate cohesiveness (0.87 ± 0.01). SC30 formulation exhibited long-term release. Thus, SC30 gel was evaluated for its clinical effectiveness along with marketed metronidazole gel. At the end of the study (42 days of clinical studies), both formulations were found to significantly reduce the probing depth, plaque index, gingival index, calculus criteria, and bleeding index. However, the SC30 gel was more effective in reducing the above parameters than marketed metronidazole gel. This study confirmed the acceptability and effectiveness of satranidazole gel for treatment of periodontitis. © 2009 American Association of Pharmaceutical Scientists.